2017
DOI: 10.1371/journal.pone.0190152
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq differential expression analysis: An extended review and a software tool

Abstract: The correct identification of differentially expressed genes (DEGs) between specific conditions is a key in the understanding phenotypic variation. High-throughput transcriptome sequencing (RNA-Seq) has become the main option for these studies. Thus, the number of methods and softwares for differential expression analysis from RNA-Seq data also increased rapidly. However, there is no consensus about the most appropriate pipeline or protocol for identifying differentially expressed genes from RNA-Seq data. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
372
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 494 publications
(384 citation statements)
references
References 49 publications
5
372
2
5
Order By: Relevance
“…As the differential gene expression analysis methods currently available varied in performance (Schurch et al 2016;Costa-Silva et al 2017), we chose to combine several methods. Analysis contrasting the gene expression level between our 12 male and female individuals were thus performed using three R packages (i) DEseq2 version 1.10.1 (Love et al 2014), (ii) EdgeR version 3.26.9 (Robinson et al 2010) both relying on negative binomial distribution of read count modelling and (iii) limma-voom version 3.26.9 (Ritchie et al 2015) based on log-normal distribution modelling to take into account the sampling variance of small read counts.…”
Section: Identifying Sex-biased Genesmentioning
confidence: 99%
“…As the differential gene expression analysis methods currently available varied in performance (Schurch et al 2016;Costa-Silva et al 2017), we chose to combine several methods. Analysis contrasting the gene expression level between our 12 male and female individuals were thus performed using three R packages (i) DEseq2 version 1.10.1 (Love et al 2014), (ii) EdgeR version 3.26.9 (Robinson et al 2010) both relying on negative binomial distribution of read count modelling and (iii) limma-voom version 3.26.9 (Ritchie et al 2015) based on log-normal distribution modelling to take into account the sampling variance of small read counts.…”
Section: Identifying Sex-biased Genesmentioning
confidence: 99%
“…While most studies comparing RNA-seq analysis pipelines have focused on benchmarking the normalisation and statistical testing of DE (6,21,28,29), we elected instead to focus on the joint effects sequencing noise and of analytical noise derived from alignment and count estimation methods on DE calls. A previous study evaluating the impact of alignment methods on the DE analysis, without taking into account the presence or extent of technical noise, explored these methods in combination with a single read quantification tool (30). We have shown that a vast proportion of variability in the final output introduced by computational choices is attributable to the read quantification tool.…”
Section: Discussionmentioning
confidence: 98%
“…We conducted the simulations against these methods to illustrate the need for new approaches to study single-subject transcripts in TCWR conditions. In addition, a true gold standard to evaluate iDEG and other methods is not as simple as obtaining replicates and running conventional methods as pointed out by recent papers 34,35 .…”
Section: Proportions Of Degs Seededmentioning
confidence: 99%